The understanding of research ethics at health sciences schools in Jordan: a cross-sectional study - Nafez Abu Tarboush; Zaid Alkayed; Karem H. Alzoubi; Wael K. Al-Delaimy (BMC Medical Education, 2020)
Abstract Background Research ethics is required for high-quality research that positively influences society. There is limited understanding of research ethics in Middle Eastern countries including Jordan. Here, we aim to investigate the level of understanding of research ethics principles among health sciences faculty members in Jordan. Methods This is a cross sectional study where faculty members from the University of Jordan were surveyed for their knowledge and, attitude of research ethics principles. The study was conducted in the period between July 2016 to July 2017 using a customized-design questionnaire involving demographic data and participants’ contributions toward research, and assessment of participants’ knowledge, belief and attitude towards research ethics. Different question-formats have been used including multiple-choice, yes or no, and a four point Likert-type questions. Obtained responses were tabulated according to gender, academic-rank, and knowledge about research ethics principles. Results The study had a response rate of 51%. Among the 137 participants of this study, most (96%) were involved in human and animal research, yet, only 2/3 had prior training in research ethics. Moreover, 91% believed that investigators should have training in research ethics and 87% believed that there should be a mandatory postgraduate course on that. The average correct scores for correct understanding of researchers towards research ethics was 62%. Yet, there were some misconceptions about the major ethical principles as only 43% identified them correctly. Additionally, the role of research ethics committees was not well understood by most of the respondents. Conclusions Although there is acceptable knowledge about research ethics, discrepancies in understanding in research ethics principles seems to exist. There is a large support for further training in responsible conduct of research by faculty in health sciences in Jordan. Thus, such training should be required by universities to address this knowledge gap in order to improve research quality and its impact on society.